If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 6c = 96 Solving 12 + 6c = 96 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6c = 96 + -12 Combine like terms: 12 + -12 = 0 0 + 6c = 96 + -12 6c = 96 + -12 Combine like terms: 96 + -12 = 84 6c = 84 Divide each side by '6'. c = 14 Simplifying c = 14
| 16=5-n | | 18+6z=-3 | | 9e-12=96 | | 2(4-3x)=-16 | | -2(x+5)+5=6(x+2)+9 | | 3a=5a+6 | | 18z+6z=-3 | | 13t+-2t=11 | | (1/3)(y+11)=3y-5(y-4) | | 2(t-2)=26 | | 4x+17=89-4x | | 6p=38 | | 21x+31=15x-4 | | 2(u-14)-4=16 | | 100=b^2*81 | | -x-4y+5z=-21 | | 2xy-2y-2x=0 | | (2/3)(2x+5)=2(1-3x)+16 | | 6x+5=5x+8 | | -3(m-6)=-6 | | 2(x-4)5x=7 | | 6x+18=28-4x | | 3x-32=2(40-x) | | 4x+58=10+13 | | n^2+n+92=0 | | 3g=8-7g | | 34+13x=30+22x | | 0.9x-0.3(6-x)=2.4 | | n/10=3/5 | | pn=55 | | 13=-3(21-b)+2(b-2) | | 10x+7=4x-31 |